The effect of performance-based assessment on academic resilience, motivation, and teacher support in virtual versus non‑virtual classes - Mahan Yaghoubi; Abbas Pourhosein Gilakjani; Gholam-Reza Abbasian (Language Testing in Asia)
Abstract This study investigates the effects of performance-based assessment (PBA) on academic resilience (AR), motivation, and teacher support (TS) in online and traditional classroom settings. Guided by self-determination theory (SDT) and sociocultural theory (SCT), this research employs a quasi-experimental pretest–posttest design with 120 students across both instructional modes. Nonparametric tests, including the Mann–Whitney U and Wilcoxon signed ranks, validated the results, highlighting significant gains in AR, motivation, and TS in both groups, with more substantial improvements observed in the online setting. Spearman’s correlation analysis revealed strong positive relationships between AR, motivation, and TS, suggesting that PBA fosters an interconnected, supportive learning experience particularly effective in online environments, where digital platforms’ flexibility can significantly support learner development. Qualitative reflections drawn from participants’ journal entries, analyzed thematically, further revealed the intervention’s positive psychological and social impact, particularly in terms of emotional engagement and perceived teacher support. These results indicate that PBA is particularly effective in fostering student resilience and motivation, supported by enhanced teacher involvement. These results highlight the role of TS in enhancing PBA’s effectiveness, particularly in online environments where it helps students stay motivated and resilient. This study offers meaningful implications for educators and policymakers aiming to optimize assessment methods across instructional settings.